Biodegradable PLA-Kenaf fibre biocomposite for cleaner environment - Anuar, Hazleen; Ahmad, Zuraida; F., Fuad (ASM, 2010)
This project was undertaken to study the biodegradability of PLA-KF biocomposite in different conditions; soil burial and immersion in water. The samples were buried in soil for 40 days to investigate the degradability of biocomposites. As for water absorption tests, the samples were immersed in three different types of water which were river water (pH 6), tap water (pH 7) and sea water (pH 7.5). The amount of water intake was weighed for every three days for 27 days. This is done to determine the rate of water absorption and the effect on the physical properties of biocomposites. From the soil burial tests, it was found that longer time of soil burial and higher reinforcement of kenaf fibre has increases the weight loss of PLA biocomposite. Further, it was predicted that biodegradability may be increased up to 34.5% by prolong the burial of reinforced PLA biocomposite in the soil up to 80 days.